Vonoprazan: A Novel Potassium-Competitive Acid Blocker in the Management of H. pylori Infection and Acid-Related Disorders - Joseph, Shilpa Clara; Subramanian, Ramaswamy; Prasad, Shiva; Mamadapur, Mahabaleshwar (International Journal of Pharmaceutical Investigation, 2025)
Background Vonoprazan is a novel PCAB and the first in its class to receive US FDA approval for the treatment of H. pylori infection and gastric acid-related disorders. It binds directly to the proton pumps, blocking the exchange of potassium ions for hydrogen ions, thereby preventing the secretion of gastric acid. Vonoprazan represents a new class of medications designed to provide more consistent and reliable control of gastric acid secretion. Materials and Methods This article searched databases like PubMed, Google Scholar, ScienceDirect, Web of Science and Medline using keywords such as “vonoprazan,” “PCABs,” and “H. pylori infection.” Recent, high-quality research was prioritized during the screening process. Results and Discussion Research studies showed that vonoprazan demonstrated superior acid suppression compared to traditional Proton Pump Inhibitors (PPIs) and was found to be highly effective in eradicating Helicobacter pylori infection. The drug was effective and associated with mild and manageable adverse events compared to those seen with PPIs. Vonoprazan is generally well-tolerated in patients with mild to moderate renal and hepatic impairment. It is primarily metabolized by the CYP3A4 enzyme, which results in fewer drug interactions. Conclusion Vonoprazan is a safe and effective medication that provides faster, more potent and longer-lasting gastric acid suppression compared to conventional PPIs.
Keywords: Vonoprazan; Potassium-Competitive Acid Blocker; Proton Pump Inhibitors; Gastroesophageal Reflux Disease